Investigación traslacional para el desarrollo de la fitoterapia en Perú - Aranzábal-Alegría, German; Quiñones-Laveriano, Dante M.; Verastegui-Diaz, Araseli; Robles-Esquerre, Juana M. (Revista de Gastroenterología del Perú, 2016)
-